EDUCATIONAL AND PROFESSIONAL PATHWAY “VOCATIONAL EDUCATION – UNIVERSITY (FULL-TIME)” FOR STUDENTS IN TEACHER TRAINING PROGRAMS - Sergei A. Kremen; Faina M. Kremen (Russian Journal of Education and Psychology)
Background. With an increase in the number of school graduates entering the institutions of the vocational education system, and an increase in the variability of educational and professional trajectories of young people in general, the relevance of studying students who came to university after graduating from college increases. The question of the reasons for the admission of such students to full-time education and the possibilities of their professional development remains poorly understood.